2005
DOI: 10.5194/angeo-23-487-2005
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the field-aligned currents associated with a large-scale ULF wave using data from CUTLASS and FAST

Abstract: Abstract. On 14 December 1999, a large-scale ULF wave event was observed by the Hankasalmi radar of the Super-DARN chain. Simultaneously, the FAST satellite passed through the Hankasalmi field-of-view, measuring the magnetic field oscillations of the wave at around 2000 km altitude, along with the precipitating ion and electron populations associated with these fields. A simple field line resonance model of the wave has been created and scaled using the wave's spatial and temporal characteristics inferred from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
2
4
0
Order By: Relevance
“…This vortex was at high latitudes (MLATs 74-75 • ), which gives us reason to believe that the vortex is a combined signature of morning-sector large-scale R1 and FLR FACs. Meridional sequences of two or three vortices with opposing rotation directions (upward and downward currents) which are more consistent with previously reported FLR FAC systems (Scoffield, et al, 2005;McPherron, 2005) appear in our equivalent current patterns too, but also in these structures the most poleward FAC was typically downward, i.e., parallel to morning-sector R1.…”
Section: Summary and Concluding Remarkssupporting
confidence: 78%
See 2 more Smart Citations
“…This vortex was at high latitudes (MLATs 74-75 • ), which gives us reason to believe that the vortex is a combined signature of morning-sector large-scale R1 and FLR FACs. Meridional sequences of two or three vortices with opposing rotation directions (upward and downward currents) which are more consistent with previously reported FLR FAC systems (Scoffield, et al, 2005;McPherron, 2005) appear in our equivalent current patterns too, but also in these structures the most poleward FAC was typically downward, i.e., parallel to morning-sector R1.…”
Section: Summary and Concluding Remarkssupporting
confidence: 78%
“…The latitude of resonant field lines can be located with data from a meridional ground-based magnetometer chain: the amplitude of oscillations is largest and the phase has a change of 180 • at the FLR footpoint. In this region also the variations in the ionospheric electric field are strongest (Scoffield et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For downward currents, it is not clear how two‐dimensional cross‐sectional structure (perpendicular to B ) maps from the ionosphere to the magnetosphere. FAST‐SuperDARN conjunctions have shown how large latitudinal scales in the ionosphere (several 100s km) contain fragmented structures of ∼50 km at 4000 km altitude [ Scoffield et al , 2005, 2007]. Whether these fragmented structures are translationally invariant in longitude, or isolated flux tubes, is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Recent observations have shown that our view of a ULF wave depends upon how we choose to observe it. For example, Scoffield et al [2005] show how the latitudinal scale in radar data can be several 100 km, while in FAST data the same event has structure at 50 km. The latter scale is roughly 10λ e , where λ e is the electron inertial length (λ 2 e = m e /µ 0 ne 2 ) and is 5 km for n = 1 cm 3 (n is the magnetospheric number density).…”
Section: Observationsmentioning
confidence: 99%